EXPLORING MOTIVATIONAL FACTORS BEHIND ALCOHOL CONSUMPTION: APPROACH TO TAILORED MARKETING - Kumar Goyal, Anil; Sufi, Tahir; Krishna Chaudhary, Hare (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
This paper offers a comprehensive summary of the debates and insights within the scientific discussion on the motivations behind drinking cultures, specifically focusing on factors driving alcohol consumption among millennials. The primary objective of research is to identify the motivational factors that encourage millennials to consume alcoholic beverages. Systematization of existing literature and approaches to addressing consumption trends among millennials. The drinking habits are influenced by parental, peer, societal pressures, emotional and psychological needs. These patterns show that millennials turn to alcohol as a coping mechanism for stress and failure, with consumption frequently linked to socialization and stress relief. The knowledge of these factors is critical to developing effective marketing strategies for the millennial segment. This research may help create effective and relevant marketing strategies that connect with millennials’ reasons for drinking. The paper, titled “Exploring Motivational Factors Behind Alcohol Consumption: Approach to Tailored Marketing” follows a structured and logical sequence to present its findings.